Effects of visual feedback–guided core stabilization on transversus Abdominis function and sprint performance in elite collegiate sprinters - An, Jong-Min; Lee, Phil-Ku (Edelweiss Applied Science and Technology, 2026)
Sprinting efficiency depends on rapid force production and coordinated transfer of ground reaction forces between the lower limbs and the trunk. The transversus abdominis (TrA) stabilizes the deep core and facilitates segmental control of spinal function and regulation of intra-abdominal pressure. An impairment in the function of this muscle results in inefficient force transfer and performance deficits in sprint athletes. This randomized controlled trial investigated the effects of a visual-feedback–based core stabilization program on TrA function, lower-limb isokinetic strength, and 100-meter sprint performance in elite male collegiate sprinters. Twenty-two athletes were assigned to either a visual-feedback core exercise group or a standard core exercise group, and both groups performed a 12-week intervention consisting of three sessions per week. TrA activation was assessed using surface electromyography, TrA thickness was measured via ultrasound, and quadriceps and hamstring concentric peak torque at 180°/s was evaluated using an isokinetic dynamometer. Sprint performance was judged based on the fastest time across three 100-meter trials. The visual-feedback group showed significantly greater increases in TrA activation and TrA thickness than the standard core exercise group (p < 0.05). Both groups demonstrated improvements in quadriceps and hamstring strength, although enhancements were more pronounced in the visual-feedback intervention. Only the visual-feedback group showed a significant reduction in the 100-meter sprint time (p < 0.05), indicating effective translation of physiological adaptations to sport-specific performance. These findings suggest that visual-feedback–guided core stabilization may enhance deep trunk function, lower-limb force generation, and competitive sprint performance in elite athletes.